State of the UK Climate in 2025 - Mike Kendon; Amy Doherty; Dan Hollis; Emily Carlisle; Stephen Packman; Nick Rayner; Ségolène Berthou; Lucy Barker; Steve Turner; Jamie Hannaford; Svetlana Jevrejeva; Andrew Matthews; et al. (International Journal of Climatology, 2026)

State of the UK Climate in 2024 - Mike Kendon; Amy Doherty; Dan Hollis; Emily Carlisle; Stephen Packman; Svetlana Jevrejeva; Andrew Matthews; Joanne Williams; Judith Garforth; Tim Sparks (International Journal of Climatology, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

State of the UK Climate 2023 - Mike Kendon; Amy Doherty; Dan Hollis; Emily Carlisle; Stephen Packman; Mark McCarthy; Svetlana Jevrejeva; Andrew Matthews; Joanne Williams; Judith Garforth; Tim Sparks (International Journal of Climatology, 2024)

Ethnicity, socioeconomic status, income inequality, and colorectal cancer outcomes: evidence from the 4C2 collaboration - Cathy J. Bradley; Amy Anderson-Mellies; Evelinn A. Borrayo; Jennifer Anne Doherty; Omar A. Escontrías; David O. Garcia; Shiraz I. Mishra; Andrew L. Sussman; Cynthia A. Thomson; David W. Wetter; Linda S. Cook (Cancer Causes & Control, 2022)

Distinguishing zooplankton fecal pellets as a component of the biological pump using compound‐specific isotope analysis of amino acids - Shannon C. Doherty; Amy E. Maas; Deborah K. Steinberg; Brian N. Popp; Hilary G. Close (Limnology and Oceanography, 2021)
Zooplankton contribute a major component of the vertical flux of particulate organic matter to the ocean interior by packaging consumed food and waste into large, dense fecal pellets that sink quickly. Existing methods for quantifying the contribution of fecal pellets to particulate organic matter use either visual identification or lipid biomarkers, but these methods may exclude fecal material that is not morphologically distinct, or may include zooplankton carcasses in addition to fecal pellets. Based on results from seven pairs of wild‐caught zooplankton and their fecal pellets, we assess the ability of compound‐specific isotope analysis of amino acids (CSIA‐AA) to chemically distinguish fecal pellets as an end‐member material within particulate organic matter. Nitrogen CSIA‐AA is an improvement on previous uses of bulk stable isotope ratios, which cannot distinguish between differences in baseline isotope ratios and fractionation due to metabolic processing. We suggest that the relative trophic position of zooplankton and their fecal pellets, as calculated using CSIA‐AA, can provide a metric for estimating the dietary absorption efficiency of zooplankton. Using this metric, the zooplankton examined here had widely ranging dietary absorption efficiencies, where lower dietary absorption may equate to higher proportions of fecal packaging of undigested material. The nitrogen isotope ratios of threonine and alanine statistically distinguished the zooplankton fecal pellets from literature‐derived examples of phytoplankton, zooplankton biomass, and microbially degraded organic matter. We suggest that δ 15 N values of threonine and alanine could be used in mixing models to quantify the contribution of fecal pellets to particulate organic matter.

The development of an in vitro Pig-a assay in L5178Y cells - Rhiannon David; Emily Talbot; Bethany Allen; Amy Wilson; Usman Arshad; Ann Doherty (Archives of Toxicology, 2018)

Social vulnerability in the context of bushfire risk at the urban-bush interface in Sydney: a case study of the Blue Mountains and Ku-ring-gai local council areas - Daminda Solangaarachchi; Amy L. Griffin; Michael D. Doherty (Natural Hazards, 2012)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)